Pengaruh Faktor Ekonomi, Sosial, Dan Demografi Terhadap Keputusan Seseorang Yang Menjadikan Jasa Transportasi Online Berbasis Aplikasi (Go-Jek) Sebagai Pekerjaan Sampingan Di Kota Denpasar - Manuaba, Ida Ayu Reka Adnyani; Purbadharmaja, Ida Bagus Putu (E-Jurnal Ekonomi Pembangunan Universitas Udayana; Vol. 8, No. 4, April 2019, pp (703-940), 2019)
In the services of transportation online based on this app GO-JEK is increasingly many receiving by the age of work, because a variety of things that affect. A job as GO-JEK it be used as a side job and the work of the drivers GO-JEK. This study aims: 1 ) to analyse the influence of age, income, and the number of dependants is simultaneously against the decision someone To Work At Jasa Transportation Online based application on GO-JEK in the City of Denpasar, 2 ) to know the influence of age, income, and the number of dependants in partial against the decision someone To Work At the services of transportation online based application on GO-JEK in the city of Denpasar. The kind of used data in this study is the primary data analysis with Binary Logistic method. The results of research showing the whole variable free influential is simultaneously and significant against the decision someone to work on the services of transportation online based application on GO-JEK in the City of Denpasar. In the partial variable income, age, and the number of dependants, and significant positive against the decision someone to work on the services of transportation online based app on GO-JEK in the City of Denpasar.